Outcomes of isolated mitral valve surgery performed via right anterolateral thoracotomy: a single-centre experience - Huang, Liang; Yang, Yue-Hang; Xie, Chi-Yang; Chen, Si; Guo, Chao; Shi, Jia-Wei (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesThe evidence underlying thoracic and pulmonary complications and clinical outcomes after isolated mitral valve surgery performed via right anterolateral thoracotomy is inconclusive. This study retrospectively compared the postoperative thoracic and pulmonary complications and clinical outcomes of isolated mitral valve surgery performed via right anterolateral thoracotomy vs. median sternotomy.MethodsPatients data undergoing isolated mitral valve surgery in our institution were analyzed. Propensity score matching was applied to minimize differences between patients undergoing right anterolateral thoracotomy and median sternotomy. Intraoperative parameters, postoperative thoracic and pulmonary complications, and other postoperative outcomes were compared. Outpatient follow-ups were conducted.ResultsOf 711 individuals who met study criteria, 298 underwent right anterolateral thoracotomy and 413 underwent median sternotomy surgery. Propensity score matching resulted in 279 matched pairs for further analysis. Patients’ characteristics were comparable in the matched cohorts. The right anterolateral thoracotomy group had higher incidences of subcutaneous emphysema (23.3% vs. 2.9%, P < 0.001), pneumothorax (12.5% vs. 2.5%, P < 0.001), right diaphragmatic elevation (7.5% vs. 0.7%, P < 0.001), and massive pleural effusion (3.6% vs. 1.1%, P = 0.049) compared to the median sternotomy group. However, the right anterolateral thoracotomy group had lower 24-hour postoperative drainage [median (IQR), 200 (110, 350) vs. 300 (230, 415), ml; P < 0.001], postoperative red blood cell and plasma transfusion volume [median (IQR), 7.0 (4.0, 11.0) vs. 10.0 (5.5, 17.0), U; P < 0.001], ICU stay duration [median (IQR), 2 (2, 3) vs. 2 (2, 3), day; P = 0.004], and postoperative days [median (IQR), 9 (8, 11) vs. 12 (10, 15), day; P < 0.001]. Follow-up data of patients in two groups had no significant differences (P > 0.05). Multivariable logistic regression analysis revealed that incision type, age, atrial fibrillation, and coronary heart disease were significant factors influencing postoperative thoracic and pulmonary complications and course (P < 0.05).ConclusionsIsolated mitral valve surgery via right anterolateral thoracotomy was associated with more thoracic and pulmonary complications and shorter 24-hour postoperative drainage, ICU stay duration and postoperative days compared with median sternotomy, which potentially related to the choice of incision site, specific patient conditions, and surgical techniques.